Water vapor transmission and waterproofing performance of concrete sealer and coating systems - Safiuddin, Md.; Soudki, Khaled A. (Journal of Civil Engineering and Management, 2015)
This paper reports the water vapor transmission and waterproofing performance of a silane-based penetrating sealer (PS), two cementitious coatings (CC1 and CC2), and a polymeric coating (PC). The sealer and coating products were applied on 100-mm concrete cubes. In total, fifteen concrete cubes including the control specimens were prepared. The treated concrete cubes were tested to determine the ability of the selected products to improve waterproofing and to transmit water vapor. The correlation between water vapor transmission and waterproofing performance was also examined. Experimental results revealed that the cementitious coating CC2 had the lowest degree of water vapor transmission but the highest degree of waterproofing performance. In contrast, the highest degree of water vapor transmission but the lowest degree of waterproofing performance were observed for the cementitious coating CC1. The penetrating sealer PS provided greater water vapor transmission but lower waterproofing ability than the polymeric coating PC and the cementitious coating CC2. The best-performing coating with regard to water vapor transmission and waterproofing was the polymeric coating PC. Furthermore, the water vapor transmission and waterproofing performance of the sealer and coating systems were strongly correlated; this suggests that one of these two properties can be predicted by testing the other.